FREQUENCY OF CAESAREAN SECTION FOR UTERINE SCAR - Kurbaniyazova Venera Enverovna (International Engineering Journal For Research & Development, 2022)
Childbirth is the final stage of pregnancy, and the condition of the mother and the newborn child depends on the correctness of their management, and therefore new high-tech research methods are being developed for more effective management of pregnancy and childbirth. In a situation where the frequency of abdominal delivery is high, it naturally becomes necessary to analyze the indications for this operation.